Adsorption Properties and Mechanism of Cd2+ in Water by Zr-containing Silica Residue Purification - Chen, Wanting; Zhang, Han; Liang, Yu; Ding, Hao; Sun, Sijia (Frontiers in Chemistry, 2018)
Zr-containing silica residue purification discharged from industrial production of ZrOCl2 was used as adsorbent, CdCl2 solution was used as simulated wastewater containing Cd2+, the properties and mechanism of ZSR-P absorbing Cd2+ were studied. The results showed that ZSR-P had a good effect of adsorption and removal of Cd2+ in water. The adsorption time, initial concentration of Cd2+ and solution pH had a significant effect on the adsorption behavior, and pH value had the greatest effect among them. Under the optimal conditions, the amount of Cd2+ adsorbed by ZSR-P was 43.1mg/g. The isothermal adsorption conformed to the Langmuir adsorption model and the adsorption kinetics conformed to the secondary adsorption rate model. In the ZSR-P-Cd, Cd2+ was uniformly distributed on the surface of SiO2 particles and in the voids formed by the accumulation of particles. Adsorption of Cd2+ by ZSR-P was achieved through the reaction between Si-OH on the surface of SiO2 and Cd2+ hydroxyl compounds.